Proses Pengembangan Organisasi di SDN 04 2x11 Kayutanam - Ilham Rafi (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
In the era of globalization and rapid technological advancement, educational institutions are required to adapt continuously to maintain relevance and effectiveness. This study aims to analyze the organizational development process at SDN 04 2x11 Kayutanam based on modern theories of organizational change. The research employed a qualitative descriptive approach. Data were collected through interviews, observations, and document studies, then analyzed using Miles and Huberman’s model, consisting of data reduction, data display, and conclusion drawing. The results indicate that the school’s organizational development process was carried out systematically and participatively. The principal acted as a change agent by fostering collaboration, effective communication, and an innovative work culture. The findings align with Kurt Lewin’s three-stage change model (unfreezing, change, refreezing) and with Kotter’s and Bullock & Batten’s frameworks emphasizing planning and continuous evaluation. The organizational development at SDN 04 2x11 Kayutanam successfully improved work effectiveness, adaptive organizational culture, and the quality of learning. This study concludes that successful organizational change in education depends strongly on transformational leadership, collective participation, and open communication among all members of the organization.